Kiprah Pendidikan Pesantren Sebagai Pendidikan Tradisional dalam Menjawab Keterasingan Masyarakat Modern - Bahrul Ulum (Jurnal Studi Pesantren, 2020)
Pesantren education is a form of traditional education in Indonesia. Although along with the renewal and modernization of education in every pesantren education institution, the traditional values ??remain evident. Among other things, the pattern of relationships between students and teachers or more precisely students and religious teachers or to the kiai. Teaching methods and equipment have also become increasingly sophisticated, but some have remained behind. In recent times we have seen a lot of ideological content which has also undergone a very varied development, starting from various kinds of Islamic revivalism which then influenced political actions and movements such as "terrorism", which has developed in many pesantren. This is a form of reasonableness as a dialectical law between traditional education when it comes to modern developments which are then considered to be damaging to morals, beliefs, and humanity from the point of understanding of religion.